2016
DOI: 10.1002/ardp.201500457
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Rapamycin Derivatives Containing the Triazole Moiety Used as Potential mTOR‐Targeted Anticancer Agents

Abstract: Rapamycin, a potent antifungal antibiotic, was approved as immunosuppressant, and lately its derivatives have been developed into mTOR targeting anticancer drugs. Structure modification was performed at the C-42 position of rapamycin, and a novel series of rapamycin triazole hybrids (4a-d, 5a-e, 8a-e, and 9a-e) was facilely synthesized via Huisgen's reaction. The anticancer activity of these compounds was evaluated against the Caski, H1299, MGC-803, and H460 human cancer cell lines. Some of the derivatives (8a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Interestingly, it is worth to mention that the introduction of aryl‐amino‐methyl group on triazole ring, such as 7a , 7c , and 7d , also led to an obvious raise in anticancer activity while hydroxyl‐alkyl ( 7e and 7f ) caused anticancer potency to be lowered significantly. More interestingly, we had reported the synthesis and antitumor activities of C‐43 triazole‐based rapamycin derivatives, in which the side chain of compound 4a , 4b , 5e were almost the same with 6c , 6f , 7a , respectively, but the anticancer activities of 4a , 4b , 5e were much weaker, indicating that the anticancer activities of the rapalogs modified on C‐28 position were stronger than that of the rapalogs modified on C‐43 position.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, it is worth to mention that the introduction of aryl‐amino‐methyl group on triazole ring, such as 7a , 7c , and 7d , also led to an obvious raise in anticancer activity while hydroxyl‐alkyl ( 7e and 7f ) caused anticancer potency to be lowered significantly. More interestingly, we had reported the synthesis and antitumor activities of C‐43 triazole‐based rapamycin derivatives, in which the side chain of compound 4a , 4b , 5e were almost the same with 6c , 6f , 7a , respectively, but the anticancer activities of 4a , 4b , 5e were much weaker, indicating that the anticancer activities of the rapalogs modified on C‐28 position were stronger than that of the rapalogs modified on C‐43 position.…”
Section: Resultsmentioning
confidence: 99%
“…The anticancer activities of the compounds were evaluated against A549, PC‐3, CASKI, 769‐P, ECA‐109 cancer cell lines by sulforhodamine B (SRB, Sigma) assay in vitro , as described previously …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the complex structure of rapamycin, CuAAC appears to be the best strategy for the generation of novel rapamycin derivatives. For example, C42 rapamycin-triazole N4 (IC 50 = 6.05–25.88 μ M) could exert more potent inhibitory against H1299, MGC-803, H460, and Caski cancer cells than that of rapamycin (IC 50 = 18.74–35.13 μ M) ( Xie et al, 2016 ). Mechanism studies indicated that N4 could cause the change of cell morphological, and induce apoptosis of the tested Caski cells.…”
Section: Click Chemistry-based Modification Of Macrocyclic Natural Productsmentioning
confidence: 99%